Keterampilan Mengelola Konflik Remaja - Yuswati, Maria Puji Yuswati; Nuryono, Wiryo; All Habsy, Bakhrudin; Nursalim, Mochamad (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2025)
Adolescence is an important period in the formation of self-identity, personality, and social skills that determine the quality of life in adulthood. One of the challenges often experienced by adolescents is conflict, both internal and external, which if not managed properly can have a negative impact on emotional well-being and social relationships. This study aims to improve adolescents' understanding of the importance of conflict management skills and to introduce ways to develop these skills effectively. The scope of the study includes an introduction to the concept of conflict, approaches to increasing awareness and conflict management skills, and the creation of a conducive environment in schools and families. The method used is a literature review of various relevant scientific sources, including journals, articles, and books published in the last five years. The results of the review indicate that conflict management skills can be developed through character education, social skills training, and direct practice, all of which will be more effective if supported by an open and supportive environment. The development of these skills needs to be an integral part of adolescent education through collaboration between educators, counselors, and parents in order to optimally support adolescent social-emotional development